The Effect of Bibliotherapy and Videotaping Techniques on Collective and Self-Concept Formation in Behaviorally Disordered Youth - DeFrances, Janice ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The effect of bibliotherapy, videotaping, and bibliotherapy combined with videotaping techniques on the self concept of 33 behaviorally disordered adolescent males was examined. Analysis of pre- and posttest scores of the Self Observation Scale (SOS) indicated no significant difference between the treatment groups and control groups on any of the posttest SOS scales. Results failed to demonstrate any significant effect on collective and self concept formation by utilizing the designated techniques. However, observable behavioral changes were noted by researchers for all three experimental groups. (Author/CL)
ERIC Note: Paper presented at the Annual International Convention of the Council for Exceptional Children (60th, Houston, TX, April 11-16, 1982, Session T-11).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Problems; Bibliotherapy; Self Concept; Videotape Recordings; Speeches/Meeting Papers; Reports, Research